Lukisan Tabik Karya Bibit Waluya Sebagai Parodi Visual Dan Ekspresi Kritik Identitas - Anggoro, Albertus Rusputranto Ponco (Brikolase : Jurnal Kajian Teori, Praktik dan Wacana Seni Budaya Rupa, 2010)
Painting, as one form of matter creation of art works not only offer an aesthetic experience, imagination and sensory perception for their apreciations but also knowledge. The work of art seen from perspectif hermeneutics is an autonomous artistic phenomenon in the interpret-tation of meaning.To understand the hidden or latent meaning of a painting of hermeneutic theory is needed to unravel the particular text or set of potential marks. The painting, entitled adieu, the work of Seeds 'Jrabang' Â Waluya is the subject of art is interpreted by using the rules of hermeneutics to understand its role as a visual parody of criticism and expression of identity. Keywords: Painting, Works of Art, Hermeneutics, Interpretation, Pa-rody, Criticism